Comparison of the Effects of Vitagnus, Soy, and Vitagnus-soy Capsules on Premenstrual Syndrome in University Students: A Randomized Clinical Trial - Roya Partovi Golshan; Maryam Moradi; Hasan Rakhshandeh; Vahid Ghavami; Seyed Mostafa Moshirian Farahi (International Journal of Community Based Nursing and Midwifery)
Background: Premenstrual syndrome (PMS) is a common disease that negatively impacts women’s quality of life. This study aimed to compare the effects of the Vitagnus, soy, and Vitagnus-soy combination on PMS in students.Methods: This triple-blind, three-arm clinical trial was conducted on 108 students with PMS living in the dormitory of Mashhad University of Medical Sciences from September 2022 to October 2023. Eligible participants diagnosed with moderate to severe PMS over two menstrual cycles, using the Calendar of Premenstrual Experiences form, were randomly assigned to one of three groups. Each participant took one daily capsule of Vitagnus (N=36), Soy (N=36), or a Vitagnus-soy combination (N=36) for two menstrual cycles. The data were analyzed using the ANOVA test (or Kruskal-Wallis test) with post-hoc tests based on Tukey (or Bonferroni correction), Chi-square test (or Fisher’s exact method), and Wilcoxon test analysis (or paired t-test) in SPSS software version 26 with the significance level of P<0.05.Results: In all three groups, PMS symptoms significantly reduced after the intervention (P<0.001). The Vitagnus-soy combination was more effective than either Soy or Vitagnus group in decreasing psychological (P<0.001) and total PMS symptoms (P<0.001). Vitagnus-soy combination had no statistically significant difference in decreasing physical PMS symptoms compared to Soy (P>0.999), but it was more effective than Vitagnus (P<0.001).Conclusion: The Vitagnus-soy combination was more effective in alleviating PMS psychological and total symptoms than using either Soy or Vitagnus alone, making it a recommended option for reducing PMS symptoms.Trial Registration Number: IRCT2022072005514N1